2021
DOI: 10.1017/sjp.2021.36
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Two Directions of the Work–Family Interface: A Diary Study

Abstract: The work–family interface can be viewed as a process in which daily fluctuations in work demands and resources influence family functioning and behavior, and vice versa. This study aimed to test the daily processes of both directions of the work–family interface through two studies. The first study consisted of 103 male and female workers from 17 Brazilian states. The participants’ ages ranged from 20 to 61 years (M = 33.68; SD = 9.13). Each participant answered a daily questionnaire over the course of 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…One of the ways to obtain these results is to reduce the levels of perceived work demands, as the results indicated negative relationships between work demands and family well-being. These findings are consistent with other studies (Gabardo-Martins et al, 2021;Kutty, 2018). In addition, they have shown that individuals with many work demands are unable to reconcile work and family life and, consequently, do not achieve positive results in their families (Gabardo-Martins et al, 2021).…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…One of the ways to obtain these results is to reduce the levels of perceived work demands, as the results indicated negative relationships between work demands and family well-being. These findings are consistent with other studies (Gabardo-Martins et al, 2021;Kutty, 2018). In addition, they have shown that individuals with many work demands are unable to reconcile work and family life and, consequently, do not achieve positive results in their families (Gabardo-Martins et al, 2021).…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…Consistently with those assumptions, empirical studies have evidenced negative relationships of work demands with family well-being (Gabardo-Martins et al, 2021;Kutty, 2018;Skomorovsky et al, 2015). Based on these statements, the following hypothesis was formulated:…”
mentioning
confidence: 89%
“…General Job Satisfaction Scale, with validity evidence obtained by Gabardo-Martins et al (2021). This instrument is unifactorial and composed of five items to be answered using a Likert-type scale of five points, ranging from one (strongly disagree) to five (strongly agree).…”
Section: Instrumentsmentioning
confidence: 99%
“…Job satisfaction can be described as a pleasurable or positive emotional state that comes from evaluating work experiences (Gabardo-Martins, Ferreira, & Valentini., 2021). Work engagement can be characterized as a positive and fulfilling state related to work (Schaufeli, 2021).…”
mentioning
confidence: 99%
“…O suporte do supervisor oferecido à família do funcionário pode ser considerado um importante recurso do trabalho que auxilia o indivíduo a equilibrar as atividades do trabalho com as demandas familiares. Isso porque, eventualmente, a relação interface trabalho-família pode ficar comprometida à medida que problemas, como o excesso de demandas, capazes de gerar tensões e sentimentos de estresse e irritação, podem surgir e interferir negativamente na relação do funcionário com o contexto laboral e transbordar para o âmbito familiar (Gabardo-Martins et al, 2021). Portanto, comportamentos orientados dos supervisores à família do funcionário seria um importante recurso de auxílio na redução dos efeitos negativos de estressores relacionados ao trabalho e a família, o que beneficiaria o trabalhador.…”
Section: Introductionunclassified